223k views
0 votes
(2x^6/y^4)^-3 simplify

User Criel
by
5.6k points

1 Answer

2 votes

Answer:


\[(y^(12))/(8 * x^(18))\]

Explanation:

Given expression is
\[(2x^(6)/y^(4))^(-3)\]

In order to simplify the expression, we need to evaluate the numerator and denominator values when a power of -3 is applied to them individually.

Computing the numerator:


\[(2x^(6))^(-3)\]


\[=(2^(-3) * x^(6*(-3)))\]


\[=((1)/(2^(3)) * x^(-18))\]

Similarly the denominator:


\[(y^(4))^(-3)\]


\[=y^(4*(-3))\]


\[=y^(-12)\]

So the overall simplified expression is:


\[(((1)/(2^(3)) * x^(-18)))/(y^(-12))\]


\[=(y^(12))/(8 * x^(18))\]

User Puneet Sharma
by
5.1k points